Developing the Teaching Materials of Proverb Menaing with A Contructivism Aproach on Inquisitive Semantics - Hermandra Hermandra; M. Nur Mustafa; Zulhafizh Zulhafizh; Ahmad Yani T (JETL (Journal of Education, Teaching and Learning), 2023)
This study aimed to produce teaching materials for the meaning of proverbs with a constructivism approach based on inquisitive semantics for high school students. The research was conducted in the Riau Province high school equivalent. A performance test on the interpretation of constructivism approach proverbs that meets the standards of content validity was the main research instrument, along with questionnaires for teachers and a team of experts. A strategy based on constructivism and eight procedures were utilized to create instructional materials for proverbial meaning. The first is a preliminary study. Second, compiling the initial product design. Third, develop the initial product design. Fourth, initial product trials on a limited scale. Fifth, evaluation and revision of the initial product. Sixth, testing the revised product on a broad scale. Based on the study results, the pre-test on the meaning of proverbs was included in the low category, where there was no difference in the category of pre-test results per school group. A high category of post-test results on the meaning of proverbs was discovered, with disparities in the category of post-test results by a school group. There was no variation in categories per class, though. Furthermore, a substantial difference in the use of proverbs was discovered based on the findings of the pre-test and post-test. The seventh stage is to determine and revise the revised product. The eighth step is to present the final product. Because the F count value was 0.283 < the F table value which was 3.15, the test results of teaching materials were of high quality, with no significant differences in the ability to interpret proverbs. This finding suggests that the availability of teaching materials fulfills the feasibility of content, presentation, language, and graphic feasibility, and is appropriate for use in assisting in learning activities.